The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/kin.10024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and redox characteristics of semireduced species derived from phenosafranine in homogeneous aqueous and sodium dodecyl sulfate micellar media

Abstract: One-electron reduction of phenosafranine (PS + , 3,7-diamino-5-phenylphenazinium chloride), a phenazinium dye, has been studied in homogeneous aqueous and sodium dodecyl sulfate (SDS) micellar media, using the pulse radiolysis technique. The various reducing radicals employed for the study in homogeneous aqueous medium were e aq − , H · , CO 2 ·− , and isopropyl ketyl radicals (CH 3 ) 2 · COH. Semireduced species generated by these reactions have been characterized by their absorption spectra, decay kinetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…2 is lower than the one observed by conductivity, viscosity and light-scattering measurements [35]. Lowering the cmc values in dye-surfactant systems has also been observed in the past by Mukerjee and Mysels [12b,36].…”
Section: Influence Of Surfactant On the Dye Absorption Spectramentioning
confidence: 51%
“…2 is lower than the one observed by conductivity, viscosity and light-scattering measurements [35]. Lowering the cmc values in dye-surfactant systems has also been observed in the past by Mukerjee and Mysels [12b,36].…”
Section: Influence Of Surfactant On the Dye Absorption Spectramentioning
confidence: 51%
“…The same effect can be observed with opposite micelle polarity, with anionic oxidants like chromate associating to cationic micelles to oxidize compounds like D-glucose [2]. Redox reactions involving micelle-bound species like phenosafranine (PS) benefits also from this concentration effect of the charged species PS + upon SDS micelles [3], and in this case, micelle-binding of the reactants also alters the mechanism of the redox process, favoring the stability of the transient state.…”
Section: Introductionmentioning
confidence: 75%
“…In a pulse radiolysis study Mittal et al 44 reported ε R = 12 600 M −1 cm −1 at 410 nm and 11 300 M −1 cm −1 at 650 nm. Using the GSD method a lower limit of 7500 M −1 cm −1 and 8200 M −1 cm −1 at 650 and 410 nm, respectively, was obtained.…”
Section: Determination Of Radical Quantum Yieldsmentioning
confidence: 99%
“…40 The oxidation potential of indole derivatives is 1.24 V for indole and tryptophan and 1.07 V vs. SCE for 3-methyl indole. 44 Using the triplet energy of the dye, 1.77 eV, 42,43 the reduction potential vs. SCE for the triplet state of the dye may be estimated as −1.20 V in water. 44 Using the triplet energy of the dye, 1.77 eV, 42,43 the reduction potential vs. SCE for the triplet state of the dye may be estimated as −1.20 V in water.…”
Section: Triplet Quenching By Indolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation